1985
DOI: 10.1021/om00130a012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and single-crystal x-ray study of the mononuclear dihapto-benzyne (dehydrobenzene) nickel(0) complex Ni(.eta.2-C6H4)[(C6H11)2PCH2CH2P(C6H11)2]. Insertion reactions with simple molecules and x-ray crystal structure of the nickelaindan complex Ni(CH2CH2C6H4-o)[(C6H11)2PCH2CH2P(C6H11)2]

Abstract: Sodium amalgam reduction of NiC1(C6H4Br-2)(Cy2PCHzCHzPCyz)-0.5THF (6) (Cy = cyclohexyl, C6H1,) gives a mononuclear nickel(0) complex, Ni(qz-C6H4)(Cy3PCHzCHzPCy2) (3), which has been characterized by microanalysis, by mass, infrared, and NMR ('H, ' C, 31P) spectroscopy, and by single-crystal X-ray structural analysis. Crystals of 3 are orthorhombic, space group Pbca, with a = 16.068 (1) A, b = 17.189 (1) A, c = 22.358 (1) A, and 2 = 8. The structure was solved by heavy-atom methods and refined by least-squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 3 publications
(3 reference statements)
6
39
1
Order By: Relevance
“…First, AIM analysis (Table ) suggests that two isomeric forms can describe these transient complexes (Scheme ), o ‐phenylene ( I ) or o ‐benzyne ( II ) forms, as often proposed for known stable orthobenzyne complexes , . The bond paths between the metal center and the C1 and C2 carbon atoms are consistent with the metallacyclic structure ( I ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…First, AIM analysis (Table ) suggests that two isomeric forms can describe these transient complexes (Scheme ), o ‐phenylene ( I ) or o ‐benzyne ( II ) forms, as often proposed for known stable orthobenzyne complexes , . The bond paths between the metal center and the C1 and C2 carbon atoms are consistent with the metallacyclic structure ( I ).…”
Section: Resultsmentioning
confidence: 62%
“…The complex Ni(η 2 ‐ c ‐C 6 H 4 )(cyc 2 PCH 2 CH 2 PCyc 2 ) has been characterized by mass spectrometry, infrared spectroscopy, NMR spectroscopy, and X‐ray diffraction by M. A. Bennett et al (Scheme f). The authors have shown that these complexes can insert carbon monoxide, ethylene, and dimethylacetylenedicarboxylate into a Ni–benzyne bond to form nickelacycles , . Since then, new complexes of nickel(0) containing η 2 ‐4,5‐difluorobenzyne Ni((1,2‐η)‐4,5‐R 2 C 6 H 2 )L have been prepared (L: 1,2‐bis(dicyclohexylphosphanyl)ethane or bis(triethyl)phosphine, R: H, F) and their monomeric structure has been evidenced by 13 C NMR and FAB‐MS .…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical values, it is found that the optimized Ni–P bond lengths are slightly larger than the experimental values . But, the optimized Ni–C bond lengths are slightly shorter than the experimental values.…”
Section: Resultsmentioning
confidence: 79%
“…Several bis(benzyne) complexes of niobium, tantalum, molybdenum, and tungsten have been isolated from the reaction of the hexaarylmetalate anions with an excess of aryllithium . Also, organometallic compounds such as NiL 2 (C 6 H 4 )(L = PCy 3 , PiPr 3 ; Cy = cyclohexyl, iPr = isopropyl) and the η 2 ‐benzyne (dehydrobenzene) nickel(0) complex Ni(η 2 ‐C 6 H 4 ) ((C 6 H 11 ) 2 PCH 2 CH 2 P(C 6 H 11 ) 2 ) have been synthesized. The structure and bonding of Ni(C 6 H 4– n F n )(CO) 2 C 6 H 4 = benzyne ( n = 1–4) complexes have been studied theoretically …”
Section: Introductionmentioning
confidence: 99%
“…However, this procedure is not applicable to nickel, platinum and palladium complexes because they undergo reductive elimination, rather than beta elimination. Complexes 31 and 32 have been prepared by sodium amalgam reduction of the corresponding s-complex 37, as shown in Scheme 6 [6,7,24]. Aryne complexes of late transition metals are very reactive towards both nucleophiles (amines, alcohols, water) and electrophiles (iodine).…”
Section: Aryne Complexes Of Late Transition Metalsmentioning
confidence: 99%